Intensity-Duration-Frequency Curves for Flood Prevention in the Republic of Benin - Attogouinon, André; Lawin, Agnidé Emmanuel; Akpovi, Basile; Deliège, Jean-François (Indonesian Journal of Earth Sciences, 2024)
In this research, hourly rainfall recorded at 4 synoptic stations in the Republic of Benin over the period from 2006 to 2019 was used to produce intensity-duration-frequency (IDF) curves.  The aim is to determine daily rainfall heights of rare frequency and to establish intensity-duration curves for various recurrence periods. To achieve this, a frequency analysis of rainfall data was carried out using the Gumbel law more commonly used in the sub-region. IDF curves were constructed on the basis of extreme rainfall events in short observation series. R software was used to process the data. The results show a drop in the maximum annual intensity of short-duration rainfall at all stations. The lack of data sets for extreme rainfall values for short durations and sufficiently long reference periods underlines the importance of this study. It should be noted, however, that these results are not sufficient to establish a relationship between the gradual variations observed and the phenomenon of climate change.